Trace-element mobilization during Ca-metasomatism along a major fluid conduit: Eclogitization of blueschist as a consequence of fluid-rock interaction - Beinlich, Andreas; Klemd, R.; John, T.; Gao, J. (Pergamon, 2010)
In the subduction complex of the Tianshan mountains, western China, massive blueschist is cross-cut by an eclogite-facies major fluid conduit surrounded by a reaction zone which is mainly composed of omphacite and garnet. Petrological as well as geochemical evidence suggest that formation of the vein and the eclogitic selvage around the vein was caused by fluid infiltration under peak metamorphic conditions of 21 ± 1.5 kbar and 510 ± 30 °C. The combination of whole-rock with mineral trace-element data as well as mass-balance calculations indicate that substantial differences exist between the unaltered host rock and the part of the system which was altered by fluid-rock interaction. These differences include: (1) depletion of mainly large-ion lithophile elements (LILE) and Li of up to 60% relative to their concentrations in the unaltered host rock; (2) an extreme enrichment of CaO (~115%), Sr and Pb (>300%) in the altered parts of the vein-wall-rock system; (3) redistribution of heavy rare earth elements (HREE) from partly replaced rutile and recrystallized titanite in the blueschist-eclogite transition zone into newly grown garnet rims in the eclogitic selvage around the vein; (4) transformation of high Nb/Ta rutile into low Nb/Ta titanite which is associated with preferred mobilization of Nb over Ta; and (5) decoupling of Zr and Hf from Nb and Ta; the latter are depleted by ~30% relative to the unaltered blueschist host rock whereas the former are depleted by only ~10%. The prerequisite for the transformation of Ca-poor blueschist (6-7 wt.% CaO) into Ca-rich eclogite (up to 13 wt.% CaO) was the infiltration of a Ca-rich fluid. The release of trace elements can be attributed to partitioning of these elements into the passing fluid phase during dissolution-reprecipitation processes in the course of eclogitization. The reactivity of the precursor mineral assemblage and the chemical gradients between the reacting and passing fluid of the conduit are mainly responsible for trace-element mobilization in the studied samples. The suite of trace elements released upon fluid-induced eclogitization of the reactive wall-rock resembles that in island arc magmas showing strong enrichment of LIL elements, strong depletions in HFS elements and intermediate concentrations of REE. © 2009 Elsevier Ltd. All rights reserved.